Analisis Efektivitas dan Kontribusi Pemungutan Pajak Restoran dengan Pemanfaatan Financial Technology pada Badan Pendapatan Daerah Kota Makassar - Hety Kusherawaty Hety; Aulia Aulia; Firman Syah; M Hidayat (Al-Buhuts, 2023)
This study Aims to analyze the level of Effectiveness and Contribution of Restaurant Tax Collection with the Utilization of Financial Technology at the Regional Revenue Agency of Makassar City.This research uses a type of quantitative descriptive research. using Primary and Secondary data sources. The Data Analysis Method used in this study is the Effectiveness Ratio and Contribution Ratio. The results of this study indicate that: 1.) The level of effectiveness in collecting restaurant tax by Utilizing Financial Technology at the Makassar City Revenue Agency during the 2018-2022 period can be said to be very effective, with an average effectiveness rate of 110%. 2.) The average contribution of restaurant tax collection by Utilizing Financial Technology at the Regional Revenue Agency of Makassar City during the 2018-2022 period can be said to be unfavorable, with an average contribution rate of 13.87%